The existence of Emok Bank in the perspective of law number 10 of 1998 concerning banking - Lestari, Firda; Nurhayati, Ida (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The people of Parakanjaya Village have been using loans from loan sharks or what is known as